Delineation of environmentally sustainable urban settlement using GIS-based MIF and AHP techniques - Nitin Liladhar Rane; Saurabh Purushottam Choudhary; Arjun Saha; Aman Srivastava; Chaitanya Baliram Pande; Fahad Alshehri; Ranjan Roy; Okan Mert Katipoğlu; Hazem Ghassan Abdo (Geocarto International)
Choosing appropriate locations for built-up growth while maintaining natural balance has become necessary for sustainable urban planning. To this end, two multi-criteria decision-making (MCDM) approaches—the multi-influencing factor (MIF) and the analytical hierarchy process (AHP)—have been applied in this work. The MIF model results show that 23.546% of the study region was very highly suitable for newly built-up areas, and 18.786% was restricted for urban settlement, whereas, in the AHP model, 28.907% of the area was highly suitable, 17.619% was restricted for urban settlement. Finally, the dependability and efficiency of the two models used for the study area were assessed through the receiver operating curve (ROC) and area under curve (AUC) analysis. The comparative analysis demonstrates that the MIF approach (AUC 0.817) is more suitable and reliable than the AHP (AUC 0.783). The present work provides new insights to integrate GIS tools with MCDM for practical urban land suitability assessment.